2011
DOI: 10.1007/s00210-011-0612-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional properties of canine, rat, and murine histamine H4 receptors in Sf9 insect cells

Abstract: The histamine H₄ receptor (H₄R) is expressed on cells of the immune system including eosinophils, dendritic cells, and T cells and plays an important role in the pathogenesis of bronchial asthma, atopic dermatitis, and pruritus. Analysis of the H₄R in these diseases depends on the use of animal models. However, there are substantial pharmacological differences between various H₄R species orthologs. The purpose of this study was to analyze the pharmacological properties of canine, rat, and murine H₄R in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 51 publications
8
68
0
Order By: Relevance
“…That constitutive activity plays an important role in this case is proven by our previous findings with H 3 Rs, which are located on sympathetic nerve endings in the heart, where they inhibit NE release in I/R (Imamura et al, 1994). Unlike H 4 Rs, H 3 Rs have a very high constitutive activity (Schnell et al, 2011). Indeed, we had found that when hearts from H 3 R-deleted mice were exposed to I/R, NE release was greatly enhanced (Koyama et al, 2003), which substantiates the functional relevance of receptor constitutive activity.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…That constitutive activity plays an important role in this case is proven by our previous findings with H 3 Rs, which are located on sympathetic nerve endings in the heart, where they inhibit NE release in I/R (Imamura et al, 1994). Unlike H 4 Rs, H 3 Rs have a very high constitutive activity (Schnell et al, 2011). Indeed, we had found that when hearts from H 3 R-deleted mice were exposed to I/R, NE release was greatly enhanced (Koyama et al, 2003), which substantiates the functional relevance of receptor constitutive activity.…”
Section: Discussionsupporting
confidence: 56%
“…Given the anti-RAS role of H 4 Rs, one might have expected renin and NE release and arrhythmia to be enhanced when H 4 Rs were pharmacologically blocked or deleted. An explanation of why this did not occur is probably found in the very low constitutive activity of H 4 Rs in the mouse (Schnell et al, 2011). That constitutive activity plays an important role in this case is proven by our previous findings with H 3 Rs, which are located on sympathetic nerve endings in the heart, where they inhibit NE release in I/R (Imamura et al, 1994).…”
Section: Discussionmentioning
confidence: 73%
“…Observations of marked variation in the pharmacology of species orthologs of GPCRs are well known but are of particular relevance in the early stages of receptor characterization. For example, the differences in ligand affinity at the orthologs of the histamine H4 receptor (Liu et al, 2001) even led to suggestions that there might be other receptors for histamine and further detailed pharmacological characterization of various orthologs of this receptor (Lim et al, 2010;Schnell et al, 2011), and the development of early-generation ␤ 3 -adrenoceptor selective agonists was severely compromised by, at that time unappreciated, ortholog selectivity (de Souza and Burkey, 2001;Arch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Partial sequences of other species orthologs have been identified but not published. Species differences in pharmacology (ligand binding and signaling efficacy) are profound, also depending on readout systems (Nordemann et al, 2013), and several molecular features for the observed species differences have been elucidated (Liu et al, 2001b;Lim et al, 2008Lim et al, , 2010Schnell et al, 2011).Whereas proximal readout systems such as [ ]GTPS binding assays show pronounced differences between species orthologs, more distal reporter gene assays revealed less pronounced differences. Species splice isoforms have yet to be reported.…”
Section: A Receptor Structurementioning
confidence: 99%
“…However, the pharmacology of H 4 receptor ligands is not clear cut and well understood and therefore care must be taken when interpreting the results from any single ligand. For example, Schnell et al (2011) reconstituted H 4 receptor species orthologs from human, rat, mouse, and canine with the G protein heterotrimer G i a 2 b 1 g 2 plus the regulator of G protein signaling RGS19 in Sf9 insect cell membranes and measured high-affinity steady-state GTPase activity as a parameter for receptor activation. At all four H 4 receptor species orthologs, histamine acted as full agonist.…”
Section: E H 4 Receptor-selective Ligandsmentioning
confidence: 99%